Isolation and Structural Characterization of Ursolic Acid from Medicinal Plant Extract and Its In Silico Inhibitory Potential Against Inflammation-Linked Molecular Targets - Kumar, P. Senthil; T, Vinciya (Journal of Neonatal Surgery, 2025)
Objectives:The study aimed to isolate, characterize, and evaluate the neuroprotective and anti-inflammatory potential of a phytochemical compound from a medicinal plant. The primary objective was to assess the binding affinity of ursolic acid, a pentacyclic triterpenoid, against Alzheimer's disease-relevant protein targets using molecular docking. This included enzymes known to contribute to neuroinflammation and amyloid-beta processing, which are implicated in Alzheimer's pathology. Methods:The crude methanolic extract of the plant was subjected to gradient silica gel column chromatography, followed by purification and recrystallization, yielding a single pure compound. The structure of this compound was confirmed as ursolic acid using FTIR, ¹H-NMR, ¹³C-NMR, and mass spectrometry. Molecular docking was then performed using AutoDock Vina to explore the interaction of ursolic acid with three Alzheimer's-linked targets: Glycogen Synthase Kinase-3β (GSK-3β; PDB ID: 1H8F) Angiotensin-Converting Enzyme (ACE; PDB ID: 1O86) TNF-α Converting Enzyme (TACE; PDB ID: 3LOT) These proteins were prepared by removing heteroatoms and adding polar hydrogens. Ursolic acid was modeled and energy-minimized using ChemSketch and UCSF Chimera. Binding interactions were visualized using Discovery Studio. Result:Ursolic acid exhibited favorable binding affinities to all three protein targets involved in neuroinflammation and Alzheimer's progression. The docking results demonstrated stable hydrogen bonding and hydrophobic interactions at the active sites of GSK-3β (linked to tau phosphorylation), ACE (implicated in neurovascular dysfunction), and TACE (key in neuroinflammation via TNF-α activation). The strongest binding affinity was observed with TACE, indicating ursolic acid’s potential in modulating inflammatory cytokine release. These findings suggest that ursolic acid could attenuate both amyloid and inflammatory pathways in Alzheimer's pathology. Conclusion:This multi-approach study confirmed the identity of ursolic acid and validated its multi-target inhibitory potential against key Alzheimer’s disease-related enzymes. The compound's strong binding affinity, particularly toward TACE and GSK-3β, supports its possible use in modulating neuroinflammation, amyloid cascade, and tau hyperphosphorylation, which are hallmarks of Alzheimer's disease. The study underscores the relevance of plant-derived compounds like ursolic acid in neurodegenerative drug discovery, and supports molecular docking as a predictive tool for evaluating neuroprotective leads